FORMULASI ORALLY DISINTEGRATING TABLET (ODT) EKSTRAK ETANOL DAUN TAHONGAI (Kleinhovia hospita L.) DENGAN VARIASI KONSENTRASI EXPLOTAB® - Hayatus Sa`adah; Reni Anggraini; Sapri Sapri (JFL : Jurnal Farmasi Lampung, 2019)
Tahongai leaves (Kleinhovia hospita L.) is a medicinal plant that has antioxidant activity which is almost equivalent to vitamin C. The development of the dosage form to improve the utilization of these plants. Therefore Tahongai leaves made in the form Orally Disintegrating Tablets (ODT), which has several advantages such as more practical use because it can be consumed without the use of water and can be used by people who are hard to swallow capsules or tablets as well as having good taste in the mouth. This study was carried out experimentally using four formulas with various concentrations Explotab® ie; formula 1 (2%); formula 2 (4%); Formula 3 (6%) and the formula 4 (8%). The evaluation of ODT are uniformity of weight, hardness, friability and disintegration time.The results showed that the concentration Explotab® influence on the physical properties of ODT ie hardness, friability and disintegration time. Explotab® concentration of 4% is the best concentration that meets the requirements of the physical properties ODT Tahongai leaf extract. Keywords: Formulation, Orally Disintegrating Tablets (ODT), Explotab, Tahongai (Kleinhovia hospita L.)